Implementation of Independent Learning Curriculum for High School Students: Study on Sangihe Islands Regency - Wuisang, Jerry RH; Taroreh, Johny; Macpal, Vonny Silvia (PT. Riset Press International, 2025)
This study aims to analyze the implementation of the Independent learning curriculum for high school students in the Sangihe Islands Regency. This curriculum carries a more flexible and competency-based approach, focusing on empowering students to learn according to their interests and talents. This study uses a qualitative approach with a case study method, involving interviews with principals, teachers, and students as well as direct observation in several schools. The data collected were analyzed thematically to identify supporting and inhibiting factors in curriculum implementation. The results of the study indicate that the support of the principal and teacher readiness are the main factors supporting the implementation of the Independent learning curriculum, with several schools already utilizing technology for more interactive learning. However, the biggest challenges are the lack of teacher understanding of the basic concepts of the curriculum, limited supporting facilities, and limited time to implement project-based learning optimally. Nevertheless, students show enthusiasm for this curriculum because they get more freedom to determine how to learn according to their interests. This study suggests the need for increased training for teachers and the provision of more supportive facilities to maximize curriculum implementation. In addition, closer cooperation between the central and regional governments is essential to create more consistent and effective education policies.